2021
DOI: 10.1152/jn.00560.2019
|View full text |Cite
|
Sign up to set email alerts
|

Local spatial analysis: an easy-to-use adaptive spatial EEG filter

Abstract: Spatial EEG filters are widely used to isolate event-related potential (ERP) components. The most commonly used spatial filters (e.g. the Average Reference and the Surface Laplacian) are stationary. Stationary filters are conceptually simple, easy to use and fast to compute, but all assume that the EEG signal does not change across sensors and time. Given that ERPs are intrinsically non-stationary, applying stationary filters can lead to misinterpretations of the measured neural activity. In contrast, adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
(142 reference statements)
0
6
0
1
Order By: Relevance
“…These transformations change the voltage values at each electrode according to a weighted combination of voltage values at other (all) electrodes to highlight features that can be difficult to observe in the raw data ( Cohen, 2015 ). They also include adaptive spatial filters (e.g., independent component analysis, ICA; and principal component analysis, PCA) to rescue neural activity that can remains masked when spatial transformations consider that EEG is stationary ( Bufacchi et al, 2021 ). It is hard to know a priori which of several EEG spatial distribution reflects better a particular physiological process.…”
Section: A Multi-feature Computational Frameworkmentioning
confidence: 99%
“…These transformations change the voltage values at each electrode according to a weighted combination of voltage values at other (all) electrodes to highlight features that can be difficult to observe in the raw data ( Cohen, 2015 ). They also include adaptive spatial filters (e.g., independent component analysis, ICA; and principal component analysis, PCA) to rescue neural activity that can remains masked when spatial transformations consider that EEG is stationary ( Bufacchi et al, 2021 ). It is hard to know a priori which of several EEG spatial distribution reflects better a particular physiological process.…”
Section: A Multi-feature Computational Frameworkmentioning
confidence: 99%
“…This may explain in part the noticeable within-group and between-group variability at the fronto-central electrodes (c.f., Figures 4B and 5). Future efforts should incorporate advanced artifact removal frameworks or spatial filtering frameworks [40][41][42][43] to improve SNR given the number of EEG trials collected with this challenging recording setting. On the other hand, the Go/NoGo protocol configuration, in particular trial pace (i.e., stimulus-stimulus interval) and the probability of NoGo trials, has been reported to affect the capability to elicit prepotent motor activity and probe inhibitory control [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible to project data into subspaces expected to be associated with less noise before analysis using independent components analysis [ 18 ] or the singular value decomposition [ 19 ]. When data from multiple locations are available, spatial filtering can be used [ 20 ]. In a related technique single trial ep data over time can be extracted from noise by creating 2-D images of stacks of single traces [ [21] , [22] , [23] ] and then applying image processing techniques.…”
Section: Introductionmentioning
confidence: 99%